EP.WE.962Pre-emptive arterial stenting with covered vascular stents to prevent mycotic haemorrhage in infected fields following failed kidney and pancreas transplants prior to graft explant. (28th October 2021) - Spiers, Harry; Burke, Kelly; Anantha-Krishnan, Ganapathy; Van Dellen, David; Moinuddin, Zia; Augustine, Titus
Abstract: Aims: Allograft nephrectomy and pancreatectomy present a significant surgical challenge in contaminated surgical fields, with risks of post-operative pseudoaneurysms and mycotic bleeds. We report on our experience of prophylactic endovascular stenting shortly before or after allograft nephrectoym and pancreatectomy to reduce the risk of subsequent pseudoaneurysm formation from the donor arterial conduit. Methods: A retrospective analysis of all patients undergoing arterial stenting by interventional radiology prior to graft explant in our unit was performed. Results: Twelve patients were identified, 6 of whom had undergone kidney transplant and 6 simultaneous pancreas kidney transplant (SPK) with an average age of 46. Iliac stenting was prophylactic in 7 patients, for pseudoaneurysm (28%), graft pancreatitis (28%), acute rejection (28%), enteric anastomotic leak (16%) and transplant pyelonephritis (14%). Therapeutic stenting was performed in 5 patients, all of whom had ruptured pseudoaneurysms. Post-operative 30-day mortality occurred in 1 patient resulting from an acute on chronic limb ischaemia and subsequent sepsis and death. Of the remaining patients, none experienced complications from stenting. 9 of the 12 stented patients remain alive, with the 3 mortalities resulting from other pathology not relating to stenting. Conclusion: Prophylactic iliac stenting around the time of graft excision in inflamed or infected fields provides a safe and effective technique to completely exclude the donor arterial stump, with no subsequent vascular complications reported within our series. Preventing mycotic aneurysm formation in this way may mitigate the risk of potentially catastrophic post-operative mycotic arterial bleeds.